Understanding the mechanism of ionic gelation for synthesis of chitosan nanoparticles using qualitative techniques - Kunjachan, Sijumon; Jose, Sajan; Lammers, Twan (Asian Journal of Pharmaceutics (AJP), 2014)
We focused on qualitatively exploring the basic mechanisms involved in the Ionic gelation (IG) process, a method quite frequently used for synthesis of chitosan (CS) microparticles (MPs) and nanoparticles (NPs).We synthesized CS MPs and NPs using the Ionic gelation and microemulsion methods, and characterized the CS NPs and MPs at different stages of formulation using scanning electron microscopy (SEM) and fluorescence microscopy. Fourier Transform Infrared (FTIR) analysis was carried out to confirm effective cross-linking. Moreover, for the first time, we reported the mechanisms of IG technique for CS NP and MP synthesis with qualitative proof: (1) Complex formation of long chain oligomers with polyanions (long beaded structures) (2) cleavages at weak sites on addition of acid (HCl) (3) formation of CS NPs on chain scission.The versatility of IG for the synthesis of CS MPs and NPs was proved and compared with the microemulsion technique, thereby enhancing the wide spectrum of its use in therapeutics and biomedical applications.